KATEGORI NYERI DISMENOREA PADA SANTRI PUTRI DI PONDOK PESANTREN AL- AMIN - Siti Haniyah; Dwi Novitasari (Viva Medika, 2018)
Pain Dysmenorrhea is a physiological condition that will generally be experienced by women who aremenstruating. Painful menstruation or dysmenorrhea is a manifestation of the uterine muscle contractiondysmenorrhea Pain management is very important. Relaxation of dysmenorrhea pain is very important. The purpose of this study was to determine the pain of dysmenorrhea in female students in Pondok Pesantren Darrussalam Purwokerto. This is quasi Description Design by using sample 30 respondent The Aims of this Research was to know description of pain at dysmenorrhea at female students in Pondok Pesantren Al amin Purwokerto . Result of this study is the pain of dysmenorrhea in female students in Pondok Pesantren Darrussalam Purwokerto is heavy pain. Key Word: Description Dysmenorrhea